Fotoluminescência dos compostos (Ba1-xSrx)MoO4 sintetizados com diferentes solventes - Nogueira, Içamira Costa (Universidade Federal de São Carlos, 2013)
The molybdates with scheelite-type tetragonal structure is a family of inorganic materials that has received considerable attention since the discovery of their luminescent properties, with emission in the visible spectral region. In this work, barium strontium molybdate crystals, (Ba1-xSrx)MoO4, with the compositions (x = 0, 0.25, 0.50, 0.75 and 1) were synthesized by co-precipitation method (drop by drop) in the presence of various solvents (water, 1,4-butanediol and diethylene glycol butyl ether) . The crystals obtained were structurally characterized by X-ray diffraction (XRD), Rietveld refinement, M- Raman spectroscopy (M- Raman) and Fourier transform infrared (FT -IR) spectroscopy. The shape and size of the crystals were observed by means of field emission scanning electron microscopy (FE -SEM). The optical properties were investigated by ultraviolet-visible (UV Vis) absorption spectroscopy and photoluminescence (PL) measurements. The XRD patterns, M- Raman and FT- IR spectra showed that all crystals are monophasic with a scheelite-type tetragonal structure, belonging to the space group I41/a. The lattice parameters and atomic positions obtained by Rietveld refinement were employed to molding [BaO8], [SrO8] and [MoO4] clusters into the tetragonal lattice. The microscopy images showed that (Ba1-xSrx)MoO4 crystals with different concentrations (x) and synthesized with different solvents showed changes in size (micro and nanocrystals) and the shape (octahedron, flowers, balls and rods) crystals. Photoluminescent emission at room temperature in different regions of maximum intensity was assigned to different densities of intermediate electron levels (deep and shallow) located within the band gap as a consequence of the degree of order-disorder structural in the crystal lattice and defects on the surface of crystals. Finally, we discussed possible mechanisms to explain the behavior photoluminescent.
Photoluminescence of (Ba1-xSrx)MoO4 compounds synthesized with different solvents
Keywords: Cerâmica; Scheelita; Molibdato de estrôncio; Molibdato de bário; Rietveld, Método de; Propriedades ópticas; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA